Idiopathic Acquired Osteosclerosis in a Middle‐Aged Woman With Systemic Lupus Erythematosus. (9th May 2016) - Guañabens, Núria; Mumm, Steven; Gifre, Laia; Ruiz‐Gaspà, Silvia; Demertzis, Jennifer L; Stolina, Marina; Novack, Deborah V; Whyte, Michael P
ABSTRACT: Widely distributed osteosclerosis is an unusual radiographic finding with multiple causes. A 42‐year‐old premenopausal Spanish woman gradually acquired dense bone diffusely affecting her axial skeleton and focally affecting her proximal long bones. Systemic lupus erythematosus (SLE) diagnosed in adolescence had been well controlled. She had not fractured or received antiresorptive therapy, and she was hepatitis C virus antibody negative. Family members had low bone mass. Lumbar spine bone mineral density (BMD) measured by dual‐photon absorptiometry (DPA) at age 17 years, while receiving glucocorticoids, was 79% the average value of age‐matched controls. From ages 30 to 37 years, dual‐energy X‐ray absorptiometry (DXA) BMD Z ‐scores steadily increased in her lumbar spine from +3.8 to +7.9, and in her femoral neck from –1.4 to –0.7. Serum calcium and phosphorus levels were consistently normal, 25‐hydroxyvitamin D (25OHD) <20 ng/mL, and parathyroid hormone (PTH) sometimes slightly increased. Her reduced estimated glomerular filtration rate (eGFR) was 38 to 55 mL/min. Hypocalciuria likely reflected positive mineral balance. During increasing BMD, turnover markers (serum bone‐specific alkaline phosphatase [ALP], procollagen type 1 N propeptide [P1NP], osteocalcin [OCN], and carboxy‐terminal cross‐linking telopeptide of type 1 collagen [CTx], and urinary amino‐terminal cross‐linking telopeptide of type 1 collagen [NTx and CTx]) were 1.6‐ to 2.8‐fold above the reference limits. Those of bone formation seemed increased more than those of resorption. FGF‐23 was slightly elevated, perhaps from kidney disease. Serum osteoprotegerin (OPG) and TGFβ1 levels were normal, but sclerostin (SOST) and receptor activator of nuclear factor kappa‐B ligand (RANKL) were elevated. Serum multiplex biomarker profiling confirmed a high level of SOST and RANKL, whereas Dickkopf‐1 (DKK‐1) seemed low. Matrix metalloproteinases‐3 (MMP‐3) and ‐7 (MMP‐7) were elevated. Iliac crest biopsy revealed tetracycline labels, no distinction between thick trabeculae and cortical bone, absence of peritrabecular fibrosis, few osteoclasts, and no mastocytosis. Then, for the past 3 years, BMD Z ‐scores steadily decreased. Skeletal fluorosis, mastocytosis, myelofibrosis, hepatitis C‐associated osteosclerosis, multiple myeloma, and aberrant phosphate homeostasis did not explain her osteosclerosis. Mutation analysis of the LRP5, LRP4, SOST, and osteopetrosis genes was negative. Microarray showed no notable copy number variation. Perhaps her osteosclerosis reflected an interval of autoimmune‐mediated resistance to SOST and/or RANKL. © 2016 American Society for Bone and Mineral Research.